2006
DOI: 10.4321/s1130-01082006000800002
|View full text |Cite
|
Sign up to set email alerts
|

Is anal endosonography useful in the study of recurrent complex fistula-in-ano?

Abstract: Introduction: performing anal endosonography in complex fistula-in-ano allows us to design a personalized surgical strategy in each case, thereby improving results. However, there are doubts in the literature as to its utility in recurrent complex fistulas. The aim of this study was to compare the utility of anal ultrasonography in the study of primary versus recurrent complex fistula-inano.Patients and method: prospective study of patients diagnosed and treated for complex fistula-in-ano. Physical examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…It provides detailed anatomic definition of the fistula and its relationship to the anal sphincters, aiding the surgeon in decision making and choice of operation. [1][2][3][4][5][6][7][8] Several studies have demonstrated that the addition of H 2 O 2 as a contrast medium can provide a more detailed visualization of the anatomy, including the internal opening. [9][10][11][12] In 21 consecutive patients studied by Poen and colleagues, 12 the fistulous tract was identified correctly in 95 percent when hydrogen peroxide was used vs. 62 percent with EAUS alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides detailed anatomic definition of the fistula and its relationship to the anal sphincters, aiding the surgeon in decision making and choice of operation. [1][2][3][4][5][6][7][8] Several studies have demonstrated that the addition of H 2 O 2 as a contrast medium can provide a more detailed visualization of the anatomy, including the internal opening. [9][10][11][12] In 21 consecutive patients studied by Poen and colleagues, 12 the fistulous tract was identified correctly in 95 percent when hydrogen peroxide was used vs. 62 percent with EAUS alone.…”
Section: Discussionmentioning
confidence: 99%
“…Endoanal ultrasound (EAUS) is sometimes used to delineate the anatomy of fistulous disease and plan surgical therapy. [1][2][3][4][5][6][7][8] This imaging modality allows one to establish the relationship of the primary fistula tract to the anal sphincters, demonstrate the internal opening, differentiate a simple from a complex fistula, identify the presence of abscesses or extension into the supralevator space, and may delineate secondary tracts. However, the use of endoanal ultrasound comes with a cost.…”
mentioning
confidence: 99%
“…Performing the surgical technique or procedure with which we are most familiar is definitive, and is a decisive factor, and it is essential to have elements to support a proper diagnosis and plan the best possible course of treatment for each patient; in the literature, endoanal ultrasound is reported as a useful guide to planning a surgical strategy for each case [4]. On the other hand, nuclear magnetic resonance is a highly accurate parameter in surgery, which reduces recurrence up to 75% in patients and should be applied for this type of fistulas [5][6][7].…”
Section: Clinical and Medical Case Reportsmentioning
confidence: 99%
“…In this way, anorectal ultrasonography (ARUS) is an imaging technique that allows visualization of the rectal walls and the anal canal. Its utility is clearly defined for anorectal cancer staging, in the study of anal incontinence, and for perianal sepsis (6,7).…”
Section: Introductionmentioning
confidence: 99%